Grass - Gendry-Kim, Keum Suk; Hong, Janet; Gendry-Kim, Keum Suk. (2019)
"Grass is a powerful anti-war graphic novel, offering up firsthand the life story of a Korean girl named Okseon Lee who was forced into sexual slavery for the Japanese Imperial Army during the second World War - a disputed chapter in 20th century Asian history. Beginning in Lee's childhood, Grass shows the leadup to World War II from a child's vulnerable perspective, detailing how one person experienced the Japanese occupation and the widespread suffering it entailed for ordinary Korean folk. Keum Suk Gendry-Kim emphasizes Lee's strength in overcoming the many forms of adversity she experienced. Grass is painted in a black ink that flows with lavish details of the beautiful fields and farmland of Korea and uses heavy brushwork on the somber interiors of Lee's memories."--
"First published in 2017 by Bori Publishing Co., Korea." -- Title page verso
Keywords: Lee, Ok-sun; Child slaves -- Korea -- Biography -- Comic books, strips, etc; Child slaves -- Korea -- History -- 20th century -- Comic books, strips, etc; Child sexual abuse -- Korea -- History -- 20th century -- Comic books, strips, etc; World War, 1939-1945 -- Atrocities -- Comic books, strips, etc; World War, 1939-1945 -- Personal narratives -- Comic books, strips, etc; Korea -- History -- Japanese occupation, 1910-1945 -- Comic books, strips, etc